Teacher Questioning Strategies in English Classroom Interaction at SMA Negeri 1 Percut Sei Tuan - Sefrina Simbolon; Muthia Fitriani; Ayu Lestari; Aqsha Dinanti (Universitas Negeri Medan, 2026)
This study aimed to analyze the implementation of teacher questioning strategies in English classroom interaction at SMA Negeri 1 Percut Sei Tuan. This study applied a qualitative descriptive research design. The data were collected through classroom observation using video and audio recordings during the teaching and learning process. The data were analyzed based on the questioning strategies proposed by Wu (1993), namely rephrasing, simplification, repetition, decomposition, and probing. The findings showed that the teacher implemented all five questioning strategies during classroom interaction. Among the five strategies, decomposition became the most dominant strategy with 24 occurrences (28.2%), followed by probing with 20 occurrences (23.6%), rephrasing with 15 occurrences (17.6%), simplification with 14 occurrences (16.5%), and repetition with 12 occurrences (14.1%). The implementation of questioning strategies helped students understand the lesson more easily, encouraged students’ participation, and maintained classroom interaction during the teaching and learning process.